A Cr / CrAlSiWN gradient hard coating and preparation method thereof
By depositing Cr/CrAlSiWN gradient hard coating on the tool, the problem of degradation of existing coatings in high temperature environments is solved, and high hardness, high binding force and excellent thermal stability is achieved, which is suitable for tool applications in high temperature environments.
Patent Information
- Application Number
- CN202211315519.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-10-26
AI Technical Summary
The performance of the existing coatings has dropped sharply in high temperature environments, and the bonding force and hardness are poor, which limits the tool's working conditions and environment.
The Cr/CrAlSiWN gradient hard coating is used to deposit the Cr transition layer and the CrAlSiWN gradient layer through multi-arc ion plating technology to control the percentage of element atoms and layer thickness to form a coating with high hardness and high binding force.
Under a high temperature environment of 1100℃, the coating still maintains excellent performance, improving the tribological properties, thermal stability and high-temperature oxidation resistance of the tool, and extending the service life of the tool.
Smart Images

Figure CN115747716B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a coating and a preparation method thereof, and in particular to a Cr / CrAlSiWN gradient hard coating and a preparation method thereof. Background Art
[0002] Dry cutting, high-speed cutting, hard machining and ultra-precision machining are the development directions of CNC cutting technology today. In order to reduce production costs and achieve "green" environmentally friendly machining, more and more manufacturers choose high-speed cutting. High-speed cutting not only requires increasing the cutting speed and feed speed during metal cutting, but also extends the tool life and improves machining accuracy, which is also a requirement for precision and efficient cutting tools. Coated tools are designed to solve the problems encountered in the development of this era. They combine the carbide substrate with the hard coating very well. While ensuring the high strength and good toughness of the tool substrate, the coating material improves the high-temperature oxidation resistance, wear resistance and corrosion resistance of the carbide substrate surface, greatly optimizing the actual performance of the tool.
[0003] In recent decades, tool surface coating technology, as an emerging material surface modification technology, has been widely used in industrial production due to its excellent performance and good market adaptability. High-speed cutting industry, hard tool materials and coating technology are considered to be the three key technologies in the field of precision manufacturing.
[0004] The Chinese invention patent with publication number CN110004409 discloses a CrAlN nano gradient coating with high hardness and high bonding strength and its preparation process. The CrAlN nano gradient coating is prepared on a substrate by arc ion plating and magnetron sputtering composite plating technology. Ar gas is introduced before coating, and a bias voltage of -600 to 1000V is used to glow clean the substrate for 10 to 30 minutes. Then, the Cr target is turned on, and the bias voltage is gradually reduced to -20 to -100V, and a metal Cr transition layer is deposited for 5 to 20 minutes; N2 is introduced, and the CrN layer is deposited for 5 to 40 minutes; the Al target is turned on, and the power of the Al target is linearly increased to deposit a CrAlN nano gradient coating with continuously changing components. The CrAlN nano gradient coating involved in the present invention has a dense structure, high hardness, and a high bonding strength with the substrate. The preparation process is simple, the repeatability is good, and it is easy to industrialize.
[0005] However, existing coatings have poor bonding strength and hardness, and especially in high temperature environments, the performance of the coatings will drop sharply, which seriously limits the use conditions and environment of the tool coatings. Summary of the invention
[0006] Purpose of the invention: In order to solve the technical problems existing in the prior art, the present invention aims to provide a Cr / CrAlSiWN gradient hard coating with high hardness, high bonding strength, high temperature resistance and wear resistance, and the present invention also provides a preparation method of the Cr / CrAlSiWN gradient hard coating.
[0007] Technical solution: The Cr / CrAlSiWN gradient hard coating of the present invention comprises a Cr transition layer and a CrAlSiWN gradient layer. In the CrAlSiWN gradient layer, the atomic percentage content of each element is: Cr: 20-40at.%, Al: 50-70at.%, Si: 5-15at.%, W: 2-10at.%, and the rest is N.
[0008] Furthermore, the thickness of the Cr transition layer is 400-600 nm, and the thickness of the CrAlSiWN gradient layer is 3-6 μm.
[0009] The preparation method of the Cr / CrAlSiWN gradient hard coating of the present invention comprises the following steps:
[0010] (1) Pretreatment of metal substrate;
[0011] (2) Using a multi-arc ion plating machine for deposition treatment: Select 4 Cr targets and 8 CrAlSiW targets, heat the chamber of the multi-arc ion plating machine to 400-500°C, and evacuate to below 0.03Pa;
[0012] (3) Deposition of Cr transition layer: The vacuum degree is maintained below 0.03 Pa, 4 Cr targets are turned on, the arc current is controlled at 50-60 A, the bias voltage is controlled at 700-800 V, the duty cycle is controlled at 70-80%, argon gas is introduced, and the deposition time is 2-10 min;
[0013] (4) Deposition of CrAlSiWN gradient layer: 8 CrAlSiW targets were turned on, the arc current was controlled at 100-150 A, the bias voltage was linearly increased from 20 V-50 V to 150-200 V, the duty cycle was controlled at 60-100%, nitrogen was introduced, and the deposition time was 80-100 min;
[0014] (5) After the deposition is completed, the substrate is cooled and taken out to obtain a metal substrate on which a Cr / CrAlSiWN gradient hard coating is deposited.
[0015] Furthermore, in step (1), the metal matrix is high speed steel.
[0016] Furthermore, in step (3), the flow rate of the argon gas is 60-80 sccm.
[0017] Furthermore, in step (4), the nitrogen gas flow rate is 60-80 sccm, and the proportionality coefficient of the linear increase of the bias voltage is 0.5-3, preferably 1.
[0018] Principle of the invention: The present invention can effectively enhance the hardness, toughness, wear resistance and oxidation resistance of the coating by adding alloy elements to form multinary nitrides. By adding Si elements, a nanocomposite structure of amorphous Si3N4 encapsulating MeN nanocrystals is formed to prevent dislocation movement, thereby improving the hardness of the coating. By adding the self-lubricating element W, a WO3 phase can be formed, thereby improving the tribological properties of the coating; at the same time, the addition of the W element can also delay the formation of the w-AlN phase, thereby improving the thermal stability and high-temperature oxidation resistance of the coating. Therefore, the present invention adds Si and W elements and adopts multi-arc ion plating equipment to prepare a CrAlSiWN gradient coating with high hardness, high film-base bonding, good tribological properties, excellent thermal stability and high-temperature oxidation resistance.
[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0020] (1) The Cr / CrAlSiWN gradient hard coating of the present invention adopts a combination of a Cr transition layer and a CrAlSiWN gradient layer, has high hardness, excellent film-base bonding and tribological properties, and still has excellent performance in a high temperature environment of 1100°C, and can meet the needs of various high temperature environments;
[0021] (2) The present invention utilizes multi-arc ion plating equipment to form a coating with a gradient structure by controlling the linear increase of negative bias voltage, and obtains a coating of a desired thickness by regulating the preparation process parameters and time; compared with the prior art, the present invention can effectively reduce the complexity and cost of the manufacturing process for preparing the CrAlSiWN gradient coating, and obtain a coating with better performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the XRD pattern of the CrAlSiWN gradient layer obtained in Example 7 of the present invention;
[0023] Figure 2 This is a scanning cross-sectional view of the CrAlSiWN gradient layer prepared in Example 7 of the present invention;
[0024] Figure 3 This is a surface SEM image of the CrAlSiWN gradient layer prepared in Example 7 of the present invention;
[0025] Figure 4 This is a SEM image of the CrAlSiWN gradient layer after wear prepared in Example 7 of the present invention;
[0026] Figure 5This is a surface SME image of the CrAlSiWN gradient layer prepared in Example 7 of the present invention after annealing at 1100°C;
[0027] Figure 6 This is the EDS composition diagram of the CrAlSiWN gradient layer prepared in Example 7 of the present invention after annealing at 1100°C. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific embodiments and drawings.
[0029] Embodiment 1: The preparation method of the Cr / CrAlSiWN gradient hard coating of the present invention comprises the following steps:
[0030] (1) High-speed steel is used as the metal matrix;
[0031] (2) Use a multi-arc ion plating machine for deposition treatment: ① Open the inflation valve, clean the chamber, select 4 Cr targets with a purity of 99.99% and 8 CrAlSiW alloy targets, place the Cr targets and CrAlSiW alloy targets on the evaporation source in the chamber of the multi-arc ion plating equipment, and close the chamber door; ② Open the mechanical pump and the rough pumping valve to roughly pump the chamber, and at the same time open the molecular pump to accelerate, and close the plug valve. When the vacuum reaches 2.9Pa, open the front valve and the plug valve for fine pumping; ③ When the vacuum reaches 0.02Pa, turn on the heater, set the output power to 100%, and heat the chamber temperature to 500℃; ④ After heating, after the molecular pump is finely pumped to a vacuum of 0.03Pa, turn on the filament power supply, set the bias voltage to 400-800V, and the time is 65min. At the same time, introduce 60sccm of argon gas to clean the filament;
[0032] (3) Deposition of Cr transition layer: the vacuum degree was maintained at 0.03 Pa, four Cr targets were turned on, the arc current was controlled at 60 A, the bias voltage was controlled at 800 V, the duty cycle was controlled at 80%, argon was introduced, the deposition time was 5 min, and this was performed twice;
[0033] (4) Deposition of CrAlSiWN gradient layer: 8 CrAlSiW targets were turned on, the arc current was controlled at 100 A, the bias voltage was linearly increased from 20 V to 150 V, the duty cycle was controlled at 60%, 60 sccm of nitrogen was introduced, and the deposition time was 100 min;
[0034] (5) After the deposition is completed, the steel is cooled and taken out to obtain a high-speed steel having a Cr / CrAlSiWN gradient hard coating deposited thereon.
[0035] Example 2: The difference from Example 1 is that in step (4), the arc current is controlled at 100A, the bias voltage is linearly increased from 50V to 150V, and the duty cycle is controlled at 100%.
[0036] Example 3: The difference from Example 1 is that in step (4), the arc current is controlled at 100A, the bias voltage is linearly increased from 50V to 200V, and the duty cycle is controlled at 80%.
[0037] Example 4: The difference from Example 1 is that in step (4), the arc current is controlled at 125A, the bias voltage is linearly increased from 50V to 200V, and the duty cycle is controlled at 100%.
[0038] Example 5: The difference from Example 1 is that in step (4), the arc current is controlled at 125A, the bias voltage is linearly increased from 20V to 150V, and the duty cycle is controlled at 80%.
[0039] Example 6: The difference from Example 1 is that in step (4), the arc current is controlled at 125A, the bias voltage is linearly increased from 50V to 150V, and the duty cycle is controlled at 60%.
[0040] Example 7: The difference from Example 1 is that in step (4), the arc current is controlled at 150A, the bias voltage is linearly increased from 50V to 150V, and the duty cycle is controlled at 80%.
[0041] Example 8: The difference from Example 1 is that in step (4), the arc current is controlled at 150A, the bias voltage is linearly increased from 50V to 200V, and the duty cycle is controlled at 60%.
[0042] Example 9: The difference from Example 1 is that in step (4), the arc current is controlled at 150A, the bias voltage is linearly increased from 20V to 150V, and the duty cycle is controlled at 100%.
[0043] Comparative Example 1: The coating is CrN.
[0044] Comparative Example 2: The coating is CrAlN.
[0045] Comparative Example 3: The difference from Example 7 is that in step (4), the bias voltage increases nonlinearly.
[0046] The coatings obtained in Examples 1 to 9 and Comparative Examples 1 to 3 were subjected to performance tests. The results are shown in Tables 1 and 2.
[0047] Table 1 Summary of preparation conditions and properties of the coating obtained in Example 9
[0048]
[0049] Table 2 Summary of preparation conditions and properties of the coatings obtained in Comparative Examples 1-3
[0050]
[0051] It can be seen from Tables 1 and 2 that by adding Si and W elements, the hardness and bonding strength of the coating are greatly improved, especially when the arc current is 150 A, the hardness, bonding strength and friction coefficient of the coating all reach the optimal value. At the same time, the performance of the CrAlSiWN coating under linear bias and fixed bias is compared, and it can be seen that under the action of linear bias, the hardness and bonding strength of the gradient coating are higher, and the prepared coating is denser.
[0052] Figure 1 This is the XRD diagram of the CrAlSiWN gradient layer coating prepared in Example 7. It can be seen from the figure that the coating is mainly composed of face-centered cubic AlN, CrN, and WN phases, and the peak value tends to shift to the right as a whole. The reason is that Al and W with smaller radius occupy the position of Cr, forming a substitutional solid solution and refining the grains.
[0053] Figure 2 This is a scanning cross-sectional view of the CrAlSiWN gradient layer prepared in Example 7. It can be seen from the figure that the entire layer is composed of a Cr transition layer and a CrAlSiWN gradient layer. The coating is tightly bonded to the substrate, and the total thickness of the coating is 5.8 μm.
[0054] Figure 3 The surface SEM image of the CrAlSiWN gradient layer obtained in Example 7 shows that there are some large white particles and black pits on the coating surface, which is the most significant feature of multi-arc ion plating. The white particles are generated because high temperature is formed on the cathode surface during the coating deposition process, causing the target material to partially melt, and when deposited on the substrate surface, granular substances of different sizes are formed; the pits are generated because some large particles fall off under the negative bias of the substrate and the back sputtering, making the coating surface uneven and destroying the continuity and uniformity of the coating. The use of linear bias can better eliminate large particles and improve their size, thereby obtaining a better quality coating.
[0055] Figure 4 This is the SEM image of the CrAlSiWN gradient layer after wear prepared in Example 7. It can be seen from the figure that the surface has obvious pear-groove morphology, and the main wear mechanism of the coating is judged to be abrasive wear. After determining the composition of the worn surface by EDS, it is found that O and grinding pair components remain, so it is finally determined that the wear mechanism of the coating is abrasive wear, accompanied by a certain degree of oxidative wear and adhesive wear.
[0056] Figure 5This is the surface SME image of the CrAlSiWN gradient layer prepared in Example 7 after annealing at 1100°C. It can be seen from the figure that after annealing at 1100°C, the large particles and pits on the coating surface disappear, the overall morphology is needle-shaped, and the coating is still dense.
[0057] Figure 6 This is the EDS composition diagram of the CrAlSiWN gradient layer prepared in Example 7 after annealing at 1100°C. Table 3 is obtained from the diagram. It can be seen from Table 3 that the element composition is still mainly the coating component, and there is also a certain proportion of O element, which means that the coating has undergone a certain degree of oxidation, but the overall coating has not taken effect, and the anti-oxidation temperature is higher than 1100°C.
[0058] Table 3 Element composition of CrAlSiWN gradient coating after annealing at 1100℃
[0059]
Claims
1. A Cr / CrAlSiWN gradient hard coating, characterized in that: The gradient hard coating comprises a Cr transition layer and a CrAlSiWN gradient layer. In the CrAlSiWN gradient layer, the atomic percentage content of each element is: Cr: 20-40 at.%, Al: 50-70 at.%, Si: 5-15 at.%, W: 2-10 at.%, and the rest is N. The preparation method of the Cr / CrAlSiWN gradient hard coating comprises the following steps: (1) Pretreatment of metal substrate; (2) Using a multi-arc ion plating machine for deposition treatment: Select 4 Cr targets and 8 CrAlSiW targets, heat the chamber of the multi-arc ion plating machine to 400-500°C, and evacuate to below 0.03Pa; (3) Deposition of Cr transition layer: The vacuum degree is maintained below 0.03 Pa, 4 Cr targets are turned on, the arc current is controlled at 50-60A, the bias voltage is controlled at 700-800V, the duty cycle is controlled at 70-80%, argon gas is introduced, and the deposition time is 2-10min; (4) Deposition of CrAlSiWN gradient layer: 8 CrAlSiW targets were turned on, the arc current was controlled at 100-150A, the bias voltage was linearly increased from 20V-50V to 150-200V, the duty cycle was controlled at 60-100%, nitrogen was introduced, and the deposition time was 80-100min; (5) After the deposition is completed, the substrate is cooled and taken out to obtain a metal substrate on which a Cr / CrAlSiWN gradient hard coating is deposited.
2. The Cr / CrAlSiWN gradient hard coating according to claim 1, characterized in that: The thickness of the Cr transition layer is 400-600nm.
3. The Cr / CrAlSiWN gradient hard coating according to claim 1, characterized in that: The thickness of the CrAlSiWN gradient layer is 3-6 μm.
4. A method for preparing the Cr / CrAlSiWN gradient hard coating according to claim 1, characterized in that: The following steps are involved: (1) Pretreatment of metal substrate; (2) Using a multi-arc ion plating machine for deposition treatment: Select 4 Cr targets and 8 CrAlSiW targets, heat the chamber of the multi-arc ion plating machine to 400-500°C, and evacuate to below 0.03Pa; (3) Deposition of Cr transition layer: The vacuum degree is maintained below 0.03 Pa, 4 Cr targets are turned on, the arc current is controlled at 50-60A, the bias voltage is controlled at 700-800V, the duty cycle is controlled at 70-80%, argon gas is introduced, and the deposition time is 2-10min; (4) Deposition of CrAlSiWN gradient layer: 8 CrAlSiW targets were turned on, the arc current was controlled at 100-150A, the bias voltage was linearly increased from 20V-50V to 150-200V, the duty cycle was controlled at 60-100%, nitrogen was introduced, and the deposition time was 80-100min; (5) After the deposition is completed, the substrate is cooled and taken out to obtain a metal substrate on which a Cr / CrAlSiWN gradient hard coating is deposited.
5. The preparation method according to claim 4, characterized in that: In step (1), the metal matrix is high speed steel.
6. The preparation method according to claim 4, characterized in that: In step (3), the argon gas flow rate is 60-80 sccm.
7. The preparation method according to claim 4, characterized in that: In step (4), the nitrogen gas is introduced at a flow rate of 60-80 sccm.
8. The preparation method according to claim 4, characterized in that: In step (4), the proportionality coefficient of the linear increase of the bias voltage is 0.5-3.
Citation Information
Patent Citations
Production method of nitride coating, nitride coating and application of nitride coating
CN113564539A